Model Evaluasi Kinerja Dan Usability Sistem E-Recruitment Dengan Pendekatan Sistem Informasi - Adina Apriyani; Abdullah Ardi; Mega Wahyu Rhamadani (Riset Sinergi Indonesia (RISINDO), 2026)
The mining industry faces significant challenges in workforce recruitment due to high technical skill requirements, complex selection processes, and stringent regulations. This study develops and evaluates a web-based e-recruitment system using the Laravel framework to enhance recruitment efficiency and effectiveness. The waterfall methodology was applied in system development, encompassing requirements analysis, design, implementation, and testing, which included usability, performance, and security assessments. Usability evaluation using the System Usability Scale (SUS) resulted in a score of 85.4, indicating a high level of user satisfaction. Performance testing recorded an average response time of 1.2 seconds and a throughput of 95 requests per second, demonstrating a responsive system capable of handling high loads. Security testing via penetration testing revealed a successful attack rate of only 3.2%, indicating a high level of security. Additionally, load testing showed that the system could support up to 500 concurrent users before experiencing significant performance degradation. The findings indicate that implementing an e-recruitment system based on Laravel improves recruitment efficiency by 40% compared to conventional methods. Future development recommendations include integrating artificial intelligence for candidate matching analysis to enhance selection accuracy in the mining industry.